And harmony abound : the musical life of Morley Calvert - Kinder, Keith William (McGill-Queen's University Press, 2022)
"Morley Calvert's Suite from the Monteregian Hills is cherished by brass players worldwide and performed hundreds of times annually, making Calvert perhaps the most performed Canadian composer outside the country. Yet little is known about Calvert beyond that piece. And Harmony Abound is a thoughtful and in-depth study of a remarkably accomplished composer, conductor, and educator. Calvert made his living teaching music, but he was no ordinary high school music teacher. He was deeply committed to composing and completed some ninety works for brass ensembles, concert bands, choirs, and orchestras, while engaged in music making in the communities in which he lived. Keith Kinder traces Calvert's life story from his birth in Brantford, Ontario, in 1928 through his youth and career in Montreal, his musical involvement with the Salvation Army, his success with the famous Central Collegiate band of Barrie, Ontario, his retirement years, and his unexpected passing in Hamilton, Ontario, in 1991. Uncovering Calvert's oeuvre by analyzing representative arrangements, Kinder also documents the complete catalogue of Calvert's works, bringing to light many unpublished compositions that would otherwise be lost to performers. And Harmony Abound is a compelling picture of Morley Calvert's contribution to musical composition, education, and the cultural fabric, preserving a vital strand of the Canadian musical tapestry."--